VD_FINDINFO HC / 2013 / 396 vom 17. Juni 2013 - VD Tribunal cantonal (2013)
DÉCISION INCIDENTE, MODIFICATION DE LA DEMANDE, CONNEXITÉ MATÉRIELLE | 227 al. 1 CPC (CH), 227 al. 2 CPC (CH), 237 CPC (CH), 312 al. 1 CPC (CH)